APPRAISAL OF DATA COLLECTION FOR SCIENTIFIC REPORT IN CHEMISTRY - AANU, OYEWOBI, (IJRDO-Journal of Applied Science, 2016)
A scientific report is a document that describes the process, progress and/or result of a technicalor scientific research or the state of a technical or scientific research problem, which might alsoinclude recommendation and conclusion of the research. One of the elements of a scientificreport is the results, and it consists of data. Collecting data is a major part of any evaluation(Taylor-Powell and Steele, 1996). Before data collection, it is often necessary to check whatinformation is already available. In chemistry, data may be collected through experiments,questionnaires or participant observations (Hox and Boieje, 2005). Methods of data collectioncould be quantitative, qualitative or mixed method. Data could be primary or secondary. Thedata collected should be as accurate as ever because they either form a baseline data or they arecompared with existing values. Statistical analysis of data is usually carried out using softwareand training specialist statistics software such as SPSS (Statistics Package for Social Scientists).